2015
DOI: 10.1093/jac/dkv332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, virological and phylogenetic characterization of a multiresistant HIV-1 strain outbreak in naive patients in southern Spain

Abstract: We report a cluster of an HIV-1 strain with multiple resistance mutations that was transmitted over a period of >8 years, affecting 30 naive patients from the same geographical area. The strain was susceptible to first-line combination ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several studies have been reported in the literature about HIV genetic variability in PR and RT genes as indicators of drug resistance 13 – 15 , viral fitness 16 , and transmitted resistance 17 , 18 and as a mean to evaluate phylogenetic relationships among circulating virus 19 . However, these studies have been carried in HIV mono-infected (mi) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in the literature about HIV genetic variability in PR and RT genes as indicators of drug resistance 13 – 15 , viral fitness 16 , and transmitted resistance 17 , 18 and as a mean to evaluate phylogenetic relationships among circulating virus 19 . However, these studies have been carried in HIV mono-infected (mi) populations.…”
Section: Introductionmentioning
confidence: 99%
“…While the definition of VF varied, many included 1 or 2 consecutive measurements of "detectable" HIV-1 RNA [31,32], or 1 or 2 consecutive measurements of HIV-1 RNA > or ≥50 copies/mL [33][34][35][36][37][38][39][40][41], >200 copies/mL [40,42,43], >400 copies/mL [37,44], ≥500 copies/mL [41], and/or >1000 copies/mL [45,46] as part of study-defined VF criteria. Many did not explicitly define VF criteria [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Real-world data by regimen are described in further detail in the following sections.…”
Section: Treatment-emergent Resistance By Regimenmentioning
confidence: 99%
“…Importantly, molecular epidemiology analyses have been used to detect transmission clusters that had spread unnoticed to nonmolecular epidemiological analyses and tools [5][6][7]. Molecular epidemiology analyses have also been able to detect the expansion of drug-resistant HIV variants among the drug-naive population [8][9][10].…”
Section: Molecular Approaches To Study Hiv Epidemicsmentioning
confidence: 99%